IMPLEMENTASI MODEL PROJECT BASED LEARNING DALAM MATA KULIAH PROYEK PENELITIAN: STUDI DESKRIPTIF TENTANG KESIAPAN PENYUSUNAN SKRIPSI MAHASISWA - Yesi Maylani Kartiwi; Yusep Ahmadi F (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Students' readiness to complete an undergraduate thesis is shaped not only by their understanding of research methodology but also by their experience in conducting the entire research process throughout their academic studies. The persistent difficulties encountered by students in formulating research problems, developing research instruments, and producing scientific papers highlight the need for learning approaches that effectively bridge theoretical knowledge and research practice. This study examined the implementation of Project-Based Learning in the Research Project course and its contribution to students' readiness for thesis writing. A quantitative descriptive approach employing a survey method was conducted with 45 seventh-semester students from the Indonesian Language and Literature Education Study Program. Data were collected using a Likert-scale questionnaire measuring students' perceptions of the learning process and were analyzed using descriptive statistics, including mean scores and percentage categories. The implementation of Project-Based Learning achieved a mean score of 53 out of a maximum possible score of 60 (88.33%), indicating a high level of implementation. The learning process also strengthened the lecturer's role as a facilitator while enhancing students' critical thinking, understanding of research methodology, research instrument development, self-confidence, and academic responsibility. These findings demonstrate that Project-Based Learning contributes to improving students' readiness for thesis writing by providing authentic research-based learning experiences that systematically integrate conceptual understanding with practical research skills. ABSTRAK Kesiapan mahasiswa dalam menyusun skripsi tidak hanya ditentukan oleh penguasaan metodologi penelitian, tetapi juga oleh pengalaman menjalankan proses penelitian secara utuh selama perkuliahan. Berbagai kendala yang masih dihadapi mahasiswa dalam merancang penelitian, menyusun instrumen, dan mengembangkan karya ilmiah menunjukkan perlunya pembelajaran yang mampu menghubungkan konsep dengan praktik penelitian. Penelitian ini mengeksplorasi implementasi Project Based Learning pada mata kuliah Proyek Penelitian serta kontribusinya terhadap kesiapan mahasiswa dalam menyusun skripsi. Pendekatan deskriptif kuantitatif dengan teknik survei diterapkan kepada 45 mahasiswa semester VII Program Studi Pendidikan Bahasa dan Sastra Indonesia. Data dikumpulkan menggunakan angket skala Likert yang mengukur persepsi mahasiswa terhadap pelaksanaan pembelajaran dan dianalisis melalui statistik deskriptif berupa skor rata-rata serta persentase kategori. Implementasi Project Based Learning memperoleh skor rata-rata 53 dari skor ideal 60 atau sebesar 88,33% sehingga termasuk kategori tinggi. Pembelajaran juga memperlihatkan penguatan pada aspek peran dosen sebagai fasilitator, kemampuan berpikir kritis, pemahaman metodologi penelitian, penyusunan instrumen, serta kepercayaan diri dan tanggung jawab akademik mahasiswa. Temuan ini menegaskan bahwa Project Based Learning berkontribusi dalam membangun kesiapan mahasiswa menyusun skripsi melalui pengalaman pembelajaran berbasis riset yang mengintegrasikan pemahaman konseptual dengan praktik penelitian secara sistematis.